History and eschatology: Jesus and the promise of natural theology - Wright, N. T. (The 2018 Gifford lectures, 2019)
I.Natural theology in its historical context --1.The fallen shrine : Lisbon 1755 and the triumph of Epicureanism --2.The questioned book : critical scholarship and the Gospels --II.History, eschatology and apocalyptic --3.The shifting sand : the meanings of 'history' --4.The end of the world? : eschatology and apocalyptic in historical perspective --III.Jesus and Easter in the Jewish world --5.The stone the builders rejected : Jesus, the Temple and the Kingdom --6.The new creation : resurrection and epistemology --IV.The peril and promise of natural theology --7.Broken signposts? : new answers to the right questions --8.The waiting chalice : natural theology and the Missio Dei.